SHOCK PARACENTESIS ASSOCIATED WITH IV ALBUMIN MANAGEMENT OF CIRRHOTIC PATIENTS WITH TENSE ASCITES - A. Önder KARAOĞLU; Yıldıran SONGÜR; Nafi YAZICIOĞLU; Belkıs ÜNSAL; Himmet KARACA; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-